Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1997
DOI: 10.1115/97-gt-041
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Tip Leakage Vortices in Compressors at Flow Conditions Close to Stall

Abstract: The breakdown of tip leakage vortices at operating points close to the stability limit of transonic compressor rotors has been detected. The aerodynamic phenomenon is considered to have a major impact on stall inception. Computations have been carried out and a detailed visualization of the phenomenon is given. In addition the connection of vortex breakdown to rotating instabilities and stall is discussed. Furthermore the tip flow field of the axial rotor is compared to the results for a centrifugal and a mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…The first one is the Leading Edge Blade Tip Leakage Vortex (LEBTLV), which induces a large loss region in the middle of the passage. Many researchers [7][8][9] hypothesize that the breakdown of the LEBTLV is a probable triggering mechanism of the stall. Although the vortex breakdown has yet to happen in Figure 2, it is evident that LEBTLV is critical in the flow.…”
Section: Critical Flow Structures At Stall With Smooth Wall Configuramentioning
confidence: 99%
“…The first one is the Leading Edge Blade Tip Leakage Vortex (LEBTLV), which induces a large loss region in the middle of the passage. Many researchers [7][8][9] hypothesize that the breakdown of the LEBTLV is a probable triggering mechanism of the stall. Although the vortex breakdown has yet to happen in Figure 2, it is evident that LEBTLV is critical in the flow.…”
Section: Critical Flow Structures At Stall With Smooth Wall Configuramentioning
confidence: 99%
“…And injection can shift the position of tip leakage vortex towards downstream and thus delay the inception of stall. It has been known that tip clearance flow plays an important role in the initiation of rotating stall in axial compressors [16][17][18]. In the case of micro injection, with such tiny amount of injected air the stable compressor characteristic should not be influenced and thus could keep its shape unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (for example, see references [9] to [12]) have proposed tip leakage vortex (TLV) 'breakdown' as a possible cause of stall initiation. Hoying et al [13] suggested that the spike type of rotating disturbance might be explained by the behaviour, the TLV moving upstream of rotor as the incidence angle increased.…”
Section: Introductionmentioning
confidence: 99%